2013
DOI: 10.1371/journal.pone.0055598
|View full text |Cite
|
Sign up to set email alerts
|

Admixed Phylogenetic Distribution of Drug Resistant Mycobacterium tuberculosis in Saudi Arabia

Abstract: BackgroundThe phylogeographical structure of Mycobacterium tuberculosis is generally bimodal in low tuberculosis (TB) incidence countries, where genetic lineages of the isolates generally differ with little strain clustering between autochthonous and foreign-born TB patients. However, less is known on this structure in Saudi Arabia—the most important hub of human migration as it hosts a total population of expatriates and pilgrims from all over the world which is equal to that of its citizens.MethodologyWe exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…There was little difference between the distribution of strain lineages in both local and immigrant groups. However, the highest ratio (59.5%) of the shared strain clusters showed the typical social mixing of the resident populations [21].…”
Section: Transmission Dynamics Of Tb In Saudi Arabiamentioning
confidence: 95%
See 2 more Smart Citations
“…There was little difference between the distribution of strain lineages in both local and immigrant groups. However, the highest ratio (59.5%) of the shared strain clusters showed the typical social mixing of the resident populations [21].…”
Section: Transmission Dynamics Of Tb In Saudi Arabiamentioning
confidence: 95%
“…The majority of the isolates (81%) were imported strains including the following clades: Central Asian (CAS, 22.5%), ill-defined T clade (19.5%), East African Indian (EAI, 13.5%), Haarlem (7.5%), Latin American Mediterranean (LAM, 7.2%), Beijing (4.4%), Manu (2.7%), X (0.9%), and Mycobacterium bovis (0.9%). In addition, two clonal complexes were identified with unique spoligotyping signatures (octal codes 703777707770371, and 67777377413771), which were specific to Saudi Arabia [21].…”
Section: Molecular Epidemiology Of Mycobacterium Tuberculosis In Saudmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, transmission of drugresistant strains to a relatively higher level among the Saudi nationals and immigrants are also recently reported. 24,26 In addition, Varghese and others recently demonstrated a new trend of TB transmission particularly among newly diagnosed immigrant patients, which shows the possibility of reactivation of remote infection immediately followed by a reinfection with drug-resistant strains including MDR-TB. 27 These recent findings clearly justify that the chances of drug-resistant TB in Saudi Arabia is not only limited to acquired resistance but also to recent transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with previous studies that showed higher representation rate of Beijing, Delhi/CAS, and EAI clades among MDR isolates particularly XDR-TB. 26,40 This study has few limitations: genome sequencing techniques were not considered to reconfirm the detected mutations or to find unknown or new mutations; the elevated low resistance of moxifloxacin was not tested with higher concentrations; and due to the small size of the study group, phylogenetic analysis on transmission dynamics could not be performed.…”
Section: Discussionmentioning
confidence: 99%